Volume 3: Biomedical and Biotechnology Engineering 2016
DOI: 10.1115/imece2016-65999
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulations of Peristalsis in Unobstructed Human Ureters

Abstract: Urine is transported from the kidney to the urinary bladder through the ureter by peristalsis and pressure gradients. The contractile force acting on the ureter wall has drawn considerable interest in the field of biomechanics. Backflow of urine from bladder to the kidney can occur due to failure of the ureterovesical (ureteral-bladder) junction or blockage in the ureter passage because of recurrent urinary tract infection and also due to formation of stone in kidney. To understand the nature of the flow as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…So, the expansion bolus on the ureter wall due to the material properties, creates a slight compression zone ahead of it. As discussed earlier, a compression zone had failed to create this expansion bolus in the ureter …”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…So, the expansion bolus on the ureter wall due to the material properties, creates a slight compression zone ahead of it. As discussed earlier, a compression zone had failed to create this expansion bolus in the ureter …”
Section: Resultsmentioning
confidence: 93%
“…They later changed their model from a compressive tube to an expansive one, along with validation with their own experimental data . The current authors in a previous study also did assume a compressive force, but with the current material properties (of a human ureter), it failed to create a bolus of urine when compressed. Hence, the expansive force on the ureter wall is used here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also demonstrated a similar kind of behavior . There was a slight increase in the calculated volume flow rate compared to 2D axisymmetric studies conducted previously, including the previous works of the current authors, even though the average flow rate was comparable. The mass flow rate reported in Figure shows that backflow tendencies and mass flow rate values at inlet were similar to the work of Najafi et al…”
Section: Discussionmentioning
confidence: 99%
“…In addition, such a 2D study also justifies the previous 2D axisymmetric investigations carried out by various authors. 13,24,25,33,37…”
Section: Comparison Between 2d Axisymmetric and Full 3d Modelmentioning
confidence: 99%